RELAKSASI NAFAS DALAM MENURUNKAN KECEMASAN PASIEN PRE OPERASI BEDAH ABDOMEN - Rokawie, Agung Octa Nihando; Sulastri, Sulastri; Anita, Anita (Politeknik Kesehatan Tanjungkarang, 2017)
Anxiety is a subjective experience of a person and an emotion like an uncertain sense of concern. One of the anxiety stressors is surgery. The objective of the study was to know the effect of deep breath relaxation therapy on decreasing anxiety level in patients with pre operative abdominal surgery. This research uses pre experimental design approach with one group pretest posttest design. This research was held on April 2017 at Surgery Room of Jendral Ahmad Yani Metro City. Sampling technique using non probability sampling by purposive sampling, obtained as many as 32 respondents based on the calculation using the formula of the sample proportion estimation. Bivariate analysis using paired t test (paired sample t test). The results of this study showed anxiety level in patients with pre operative abdominal surgery before being given deep breath relaxation therapy has an average anxiety index score of 54.59 (moderate anxiety) and anxiety level in patients with preoperative abdominal surgery after being given deep breath relaxation therapy has an anxiety index score of 49.56 (mild anxiety) and a decrease of 5.03. The results of this study are expected to be a reference to the use of deep breath relaxation therapy in accordance Standard Operational Procedures to decrease anxiety levels in pre operative patients using Leaflet.